Information system capabilities and emergent competitive strategies: An investigation of the strategic fit of supply chain management information systems - McLaren, Tim (My University, 2004)
This study develops a model for analyzing fit between a firm's competitive strategies and the capabilities of their Supply Chain Management Information Systems (SCM IS). Concepts such as configurational theory, the resource based view of the firm, and emergent strategies and capabilites--all of which are underutilized in current IS literature--ground the study theoretically. A positivist case study of five manufacturers is used to explore the constructs and identify appropriate measures for operationalizing the model. The developed model enables IS planners to quickly analyze their firm's competitive strategy patterns and determine the ideal level of support required for each SCM IS capability. Firms can improve the effectiveness of their IS and reduce the risk and cost of misfits, by implementing information systems that fit their emergent competitive strategies. The developed model is a significant improvement over traditional models that advocate aligning information systems with a firm's intended strategies or their current functional requirements, both of which change more frequently than a firm's emergent competitive strategy patterns. The case study investigations yielded several important findings. First, Miles and Snow's (1978) competitive strategy typology proved useful for classifying a firm's emergent competitive strategy patterns and reducing the complexity of analysis. However, the qualitative evidence more strongly supported the use of Conant et al .'s (1990) multi-dimensional questionnaire measure of competitive strategy type rather than Miles and Snow's (1978) paragraph measure. Second, existing conceptualizations of IS capabilities were not well suited to analyzing SCM IS specifically. The findings support the conceptualization of SCM IS capabilities as the level of support provided for: operational efficiency, operational flexibility, planning, internal analysis, and external analysis. Finally, the empirical results strongly supported modeling the strategic fit of a firm's SCM IS as the amount the perceived level of support provided for each SCM IS capability was less than the theoretically ideal level, rather than the more common approach of modeling strategic fit as the absolute deviation between perceived and theoretically ideal levels.
Keywords: management science/information systems